The Behavioral Effects of tDCS on Visual Search Performance Are Not Influenced by the Location of the Reference Electrode - Ellison, Amanda; Ball, Keira L.; Lane, Alison R. (Frontiers in Neuroscience, 2017)
We investigated the role of reference electrode placement (ipsilateral v contralateral frontal pole) on conjunction visual search task performance when the transcranial direct current stimulation (tDCS) cathode is placed over right posterior parietal cortex (rPPC) and over right frontal eye fields (rFEF), both of which have been shown to be causally involved in the processing of this task using TMS. This resulted in four experimental manipulations in which sham tDCS was applied in week one followed by active tDCS the following week. Another group carried out sham stimulation in both sessions to investigate practice effects over one week in this task. Results show that there is no different between effects seen when the anode is placed ipsi or contralaterally. Cathodal stimulation of rPPC increased reaction times straight after stimulation similarly for ipsi and contralateral references. This finding does not extend to rFEF stimulation. However, for both sites and both montages, practice effects as seen in the sham/sham condition were negated. This can be taken as evidence that for this task, reference placement on either frontal pole is not important, but also that care needs to be taken when contextualising tDCS “effects” that may not be immediately apparent particularly in between-participant designs.